Cardiovascular risks in Asian HIV-infected patients receiving boosted-protease inhibitor-based antiretroviral treatment - Sakaewan Ounjaijean; Kanokwan Kulprachakarn; Linda Aurpibul; Quanhathai Kaewpoowat; Kongsak Boonyapranai; Romanee Chaiwarith; Supapong Arwon; Khuanchai Supparatpinyo; Kittipan Rerkasem (Journal of Infection in Developing Countries)
Introduction: Increased risk of cardiovascular disease in HIV-infected patients was tought to be the cause of multiple mechanistic factors, which changing the HIV care landscape. Antiretroviral therapy (ART), especially protease inhibitors (PI), is one of common HIV treatments that may have some association with this. The mechanism of PI in comparison to other regimens, however, are not clearly understood.